2012
DOI: 10.1007/s11010-012-1443-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 (miR-21) expression promotes growth, metastasis, and chemo- or radioresistance in non-small cell lung cancer cells by targeting PTEN

Abstract: MicroRNAs (miRNAs) regulate gene expression by binding to target sites and initiating translational repression and/or mRNA degradation. In our previous study, we have shown that expression of serum microRNA (miR)-21 is correlated with TNM stage and lymph node metastasis and might be an independent prognostic factor for NSCLC patients. However, the roles of miR-21 overexpression in NSCLC development are still unclear. The purpose of this study is to investigate the effect of miR-21 and determine whether miR-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
204
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(223 citation statements)
references
References 28 publications
18
204
0
1
Order By: Relevance
“…microRNA-21 has been suggested to function as an oncogene because it is overexpressed in many types of malignancy such as lung cancer (Liu et al, 2013), ovarian cancer (Iorio et al, 2007), colon cancer (Slaby et al, 2007), gastric cancer (Chan et al, 2008) and esophageal squamous cell carcinoma (Hiyoshi et al, 2009). Particularly, it had a high expression in the more aggressive PDAC cell and tissue samples .…”
Section: Discussionmentioning
confidence: 99%
“…microRNA-21 has been suggested to function as an oncogene because it is overexpressed in many types of malignancy such as lung cancer (Liu et al, 2013), ovarian cancer (Iorio et al, 2007), colon cancer (Slaby et al, 2007), gastric cancer (Chan et al, 2008) and esophageal squamous cell carcinoma (Hiyoshi et al, 2009). Particularly, it had a high expression in the more aggressive PDAC cell and tissue samples .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PTEN is a known target of miR-21. Mimics of miR-21 inhibited PTEN expression and enhanced radioresistance in non-small cell lung cancer cells (59), and inhibition of miR-21 increased radiosensitivity via PTEN in esophageal cancer (60). An additional miRNA that potentially targets PTEN is miR-205.…”
Section: Mirnas Regulating Relevant Cellular Signaling Pathwaysmentioning
confidence: 99%
“…Meng et al (2006Meng et al ( , 2007 first demonstrated that miR-21 can regulate the tumor suppressor gene PTEN in bile duct carcinoma and hepatocellular carcinoma cells and promote the invasion and migration of tumor cells, which showed that PTEN is a latent target gene of miR-21. Later PTEN was proved to be a target gene of miR-21 in other tumors (Zhang et al 2010;Li et al 2013b;Liu et al 2013 Our study determined a significantly negative correlation between the expression of miR-21 and the PTEN protein in WT tissues. The high miR-21 level had a significant correlation with age (> 24 months), UH tumor type and lymphatic metastasis; the low PTEN protein level was significantly associated with age (> 24 months), late clinical stage and UH tumor type.…”
Section: Discussionmentioning
confidence: 61%